Micronutrient dose response (MiNDR) study among women of reproductive age and pregnant women in rural Bangladesh: study protocol for double-blind, randomised, controlled trials - Tahmeed Ahmed; Hasmot Ali; Michael Rosenblum; Daniel J Erchick; Towfida Jahan Siddiqua; Rezwanul Haque; Parul Christian; Sarah Baker; Eleonor Zavala; Kerry J Schulze; SM Tafsir Hasan; Khalid Bin Ahsan; et al. (BMJ Open)
Introduction Optimising the micronutrient status of women before and during reproduction confers benefits to them and their offspring. Antenatal multiple micronutrient supplements (MMS), given as a daily tablet with nutrients at ~1 recommended dietary allowance (RDA) or adequate intake (AI) reduces adverse birth outcomes. However, at this dosage, MMS may not fully address micronutrient deficiencies in settings with chronically inadequate diets and infection. A bioefficacy study to determine amounts required to attain nutrient adequacy among women of reproductive age (WRA) and pregnant women (PW) aims to address this gap.Methods and analysis Two, four-arm, dose-response trials (n=240 participants/trial) with a double-blind, individually randomised, controlled design are underway in 18–35 year-old WRA and PW in rural northern Bangladesh. The trials will test dose response to four levels of 19 micronutrients from 1 RDA/AI up to ~75% of the tolerable upper intake level (UL), where applicable. These levels of micronutrients are delivered in the form of a reconstituted (in water) powdered drink, daily, including a placebo drink in the control arm, plus a fortified, balanced energy and protein (BEP) food product containing each micronutrient at ~1 RDA per serving. The supplement duration is 3 months in WRA and~6 months (until birth) in PW, who are enrolled at 12–16 weeks of pregnancy; women are randomised to one of the four arms at enrolment. Supplement consumption is directly observed by study staff and weekly side effects and adverse events are monitored. Blood and urine are collected at baseline, a midpoint, and at/near the end of supplementation, with a birth visit and postpartum biospecimen collection (post supplementation) for PW. Outcomes are biomarkers of nutrient status. Pharmacokinetic modelling will estimate micronutrient intakes at which sufficiency for each nutrient without excess is achieved. Enrolment was initiated on 22 October 2023.Ethics and dissemination The study was approved by the Institutional Review Board of Johns Hopkins Bloomberg School of Public Health and the research and ethical review committees of icddr,b, Bangladesh. A data safety and monitoring board is in place for the study. Findings will be disseminated in peer-reviewed papers and in-country meetings.Trial registration number NCT06081114Cite Now